2020
DOI: 10.2147/cmar.s283031
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Low and High Vacuum Drainage on the Postoperative Drainage of Breast Cancer: Insights from a Prospective, Non-Inferiority, Randomized Clinical Trial</p>

Abstract: Background: Vacuum drains have been extensively applied to prevent seroma formation after breast surgery. However, the usage of negative suction drainage is mainly determined by surgeon's experience and preferences. The aim of this study is to prospectively compare the drain effect after breast surgery between the low and high vacuum drains. Methods: This prospectively randomized trial (from January 2018 to June 2019) involved 188 patients who were subjected to modified radical mastectomy (group A, n=128) or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…On the one hand, continuous negative pressure suction can promote the formation of the capillary, provide sufficient blood supply and establish blood circulation. 29 On the other hand, continuous negative pressure suction can reduce skin tension, promote wound healing, and prevent flap necrosis. 29 At the same time, continuous negative pressure suction can also effectively prevent the spread of bacteria into the incision, and prevent the spread of bacteria into the incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, continuous negative pressure suction can promote the formation of the capillary, provide sufficient blood supply and establish blood circulation. 29 On the other hand, continuous negative pressure suction can reduce skin tension, promote wound healing, and prevent flap necrosis. 29 At the same time, continuous negative pressure suction can also effectively prevent the spread of bacteria into the incision, and prevent the spread of bacteria into the incision.…”
Section: Discussionmentioning
confidence: 99%
“… 29 On the other hand, continuous negative pressure suction can reduce skin tension, promote wound healing, and prevent flap necrosis. 29 At the same time, continuous negative pressure suction can also effectively prevent the spread of bacteria into the incision, and prevent the spread of bacteria into the incision. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The use of drains in MRM is one of the most investigated techniques aiming to reduce seroma formation (11,12). Seroma is the most common complication seen after mastectomy and axillary surgery with an incidence of 3-85%, which ultimately leads to wound problems such as impaired healing, dehiscence and infections (13).…”
Section: Discussionmentioning
confidence: 99%
“…Seroma is the most common complication seen after mastectomy and axillary surgery with an incidence of 3-85%, which ultimately leads to wound problems such as impaired healing, dehiscence and infections (13). There are still controversies regarding the number of drains, duration of drainage, and whether these drains should be at all used in breast cancer surgery (7,9,11). Previously conducted studies have not shown that double drains yield better outcomes than a single drain (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…Embora exista uma variedade de técnicas descritas para reduzir a formação de seroma, a colocação do dreno no intraoperatório é considerada o padrão ouro para evitar essa complicação 10 . No entanto, isso pode causar dor, aumento do tempo de internação ou redução da qualidade de vida dos pacientes 11 .…”
Section: Introductionunclassified